A Case of Right Temporal Lobectomy for Brain Tumor With Selective Semantic Pictorial Disorder. Issue 1 (March 2020) - Gainotti, Guido; Bonnì, Sonia; Maiella, Michele; Carretta, Jessica; Zigiotto, Luca; Sarubbo, Silvio; Papagno, Costanza
Abstract : Disagreement exists regarding representational and connectionist interpretations of semantic knowledge subserved by the right versus left anterior temporal lobes (ATLs). These interpretations predict a different pattern of impairment in patients with a right unilateral ATL lesion. We conducted a neuropsychological study of a selective semantic pictorial defect exhibited by a 57-year-old man who had undergone a right temporal lobectomy due to the presence of a glioblastoma. The patient was given the Thematic and Taxonomic Semantic task, in which individuals must select, within triplets of words or pictures, the best associates of living or nonliving stimuli, related by thematic or taxonomic links, and presented in the verbal or pictorial modality. The selectivity of the defect was documented by a comparison between the results obtained by our patient and those obtained by healthy controls on living items and on pictures with a thematic relation. The selectivity of the defect was confirmed by a within-subject analysis of the results obtained on all of the task's triplets and those obtained on the stimuli representing living entities with a taxonomic relation. The selectivity of this semantic pictorial defect mainly concerning living entities is consistent with the representational account of semantic defects observed in our patient. In the present case report, a right temporal lobectomy resulted in a selective semantic pictorial defect with the qualitative features predicted by the representational account of semantic defects observed after a unilateral ATL lesion.